2021
DOI: 10.1016/j.humpath.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The cutoff for estrogen and progesterone receptor expression in endometrial cancer revisited: a European Network for Individualized Treatment of Endometrial Cancer collaboration study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Aside from its predictive relevance, PR IHC expression is also a strong prognostic marker potentially impacting response to hormonal therapy and outcome in cases with PR-negative disease. 19,20 In our study, 50% of tamoxifen and 25% of aromatase inhibitor users had a PR IHC expression of 10%. Therefore, a larger cohort of patients with nonprogestin hormonal drugs is necessary to validate the role of PR IHC expression and ERPAS.…”
Section: Commentsupporting
confidence: 44%
See 2 more Smart Citations
“…Aside from its predictive relevance, PR IHC expression is also a strong prognostic marker potentially impacting response to hormonal therapy and outcome in cases with PR-negative disease. 19,20 In our study, 50% of tamoxifen and 25% of aromatase inhibitor users had a PR IHC expression of 10%. Therefore, a larger cohort of patients with nonprogestin hormonal drugs is necessary to validate the role of PR IHC expression and ERPAS.…”
Section: Commentsupporting
confidence: 44%
“…and J.B.) with experience in ER and PR scoring. 19 Scoring was performed blinded for clinical data. In case of disagreement, the final score was decided in a consensus meeting.…”
Section: Immunohistochemical Staining and Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of ER/PR was studied in relation to the TCGA groups and although predictive for outcome in the univariate analysis, overruled by the ProMisE subtypes in multivariate analysis [ 97 ]. Yet, cut-off values for ER/PR of 5% and 1% were used, that might have underestimated their prognostic value as Weelden, et al demonstrated the relevance of classification EC based on ER/PR into: high (0–10%), intermediate (20–80%), and low-risk (90–100%) groups [ 98 ]. A CTNNB1 mutation was more frequently detected in grade 1 and 2 EEC, though associated to a worse recurrence free survival.…”
Section: Knowledge Gaps and Possible Solutionsmentioning
confidence: 99%
“…Recognizing that hormonal receptors’ cut-offs (10%) are based on breast cancer data and, therefore, a potential source of bias, we sought to apply newer, more accurate cut-offs previously published by our group [ 11 ] pursuant to the recently published European Network for Individualized Treatment of Endometrial Cancer (ENITEC) collaboration study. The authors divided endometrial cancer into three prognostic groups based on ER/PR expression: high-risk (0–10%), intermediate-risk (20–80%) and low-risk (90–100%) [ 33 ]. Even after employing alternative cut-offs for ER, PR, and L1CAM of 88%, 78%, and 4% respectively, we did not record any significant difference between symptomatic and asymptomatic groups.…”
Section: Discussionmentioning
confidence: 99%